Manual of purpose-made woodworking joinery - Goring, L. J. (London : Routledge, 2014)
'A practical introduction to woodworking and purpose-made joinery, this book starts with the basics of interpreting drawings and works right the way through to designing and making stairs. Les Goring introduces each chapter with a brief historical overview of the topic, then goes on to explain how to carry out each task in a step-by-step manner. Including several hundred images, this book covers everything a student or keen hobbyist needs to know in order to carry out their own work.The breadth of coverage and easily accessible approach makes this book an ideal resource for apprentices taking NVQs and those following Construction Awards within Wood Occupations from City & Guilds/Construction Skills. The technical detail and practical focus ensures that this book will be a vital purchase for all students, and an essential reference for any experienced carpenter or joiner.In-depth, practical and accessible approach - ideal for new apprentices and experienced tradespeople alike.Fully up to date with the current Building Regulations and developments in the trade.Clear layout makes it easy to follow instructions.'--
Includes index.
Keywords: Joinery; Woodwork